2017
DOI: 10.1515/bhk-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on postural control and agility when wearing socks of different compression levels

Abstract: SummaryStudy aim: The aim of this study was to evaluate the effects of training while wearing socks differing in compression level (clinical, sub-clinical, regular) on performance of static and dynamic balancing and agility tasks in healthy, physically active people. We sought to understand whether socks with different compression properties supported postural regulation and agility task performance by enhancing somatosensory perception, unskewed by specific age range effects. Material and methods: Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…When statistics were performed on the whole group, our results showed that the wearing of compression garments did not significantly impact balance control. Previous studies about the effects of garments that interact with skin mechanoreceptors, such as compression garments, ankle braces, and taping, have also produced concordant findings with young, healthy, non-injured subjects and recreational sports people (Papadopoulos et al, 2007;Hijmans et al, 2009;Cavanaugh et al, 2016;Jaakkola et al, 2017;Willeford et al, 2018;Inglés et al, 2019;Medeiros Barbosa et al, 2019). Nevertheless, the clustering approach identified distinct subgroups of participants who responded differently to the wearing of compression garments.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…When statistics were performed on the whole group, our results showed that the wearing of compression garments did not significantly impact balance control. Previous studies about the effects of garments that interact with skin mechanoreceptors, such as compression garments, ankle braces, and taping, have also produced concordant findings with young, healthy, non-injured subjects and recreational sports people (Papadopoulos et al, 2007;Hijmans et al, 2009;Cavanaugh et al, 2016;Jaakkola et al, 2017;Willeford et al, 2018;Inglés et al, 2019;Medeiros Barbosa et al, 2019). Nevertheless, the clustering approach identified distinct subgroups of participants who responded differently to the wearing of compression garments.…”
Section: Discussionmentioning
confidence: 68%
“…Hence, one can assume that the effects of compression garments on balance control would be subject-dependent in active subjects. This could explain the absence of a significant effect as reported by studies about the influence of compression garments on balance control in active subjects (Hijmans et al, 2009;Cavanaugh et al, 2016;Jaakkola et al, 2017). Actually, these studies were performed with standard group ensemble average statistical approaches that do not allow to specifically address the issue of heterogeneity of individuals' postural behavior to the wearing of compression garments.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the compression feature with the length of the socks level the knee would provide greater stimulation to the lower leg mechanoreceptors where it helps the participants achieve better balance control and enhance the afferent of sensory inputs from the feet (Hasan et al, 2016). However, a previous study by Jaakkola et al (2017) on healthy participants did not find significant differences in the performance of static and dynamic balance after eight weeks' intervention program. In their study, the participants were grouped into clinical compression socks, sub-clinical and control socks group.…”
Section: Discussionmentioning
confidence: 97%
“…Only Woo et al reported a positive influence of CG with a bipedal stance when assessing elderly participants who had to perform a Romberg test on a compliant surface 15 . CG seem to preferentially benefit to subjects with lower limb injuries 12 , 23 , 24 than to non-injured subjects 17 20 . The location of the compression (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…ankle, shank, knee or thigh) does not seem to be a major factor in explaining the differences observed in the studies. Some studies reported beneficial effects of CG on balance control with knee sleeves 12 , 23 , socks 15 and leggings 13 whereas others did not report any beneficial effect with knee sleeves 17 and socks 18 20 , 22 . Similarly, the level of compression, which is not systematically specified in the studies, does not appear to be a major factor in explaining the heterogeneity of the results.…”
Section: Introductionmentioning
confidence: 99%